Enhancing Cognitive and Character Growth in Early Childhood: The Impact of the AI Edugame 'Si Robot Pintar' in Islamic Boarding Schools - Jauharotur Rihlah; Afib Rulyansah; Andini Hardiningrum (UKInstitute, 2026)
The rapid development of artificial intelligence (AI) has created new opportunities for early childhood education. However, many Islamic boarding schools (Pondok Pesantren) in Indonesia still face limitations in utilizing digital media for learning. This community service project aimed to develop and implement an AI-based educational game, “Si Robot Pintar,” designed to improve children’s critical thinking and foster positive character traits through Islamic values. The research used the ADDIE development model, involving needs analysis, design, development, implementation, and evaluation. The program was carried out in three pesantren in East Java, engaging early childhood students, teachers, and parents. Results showed significant improvements in children’s problem-solving ability, creativity, and character building, especially in honesty, cooperation, and responsibility. Teachers and parents also reported greater engagement and easier facilitation of learning. This project demonstrates that integrating AI technology with Islamic education can provide an effective and innovative approach to strengthening early childhood education in pesantren.